Deep Fashion State of Mind : An Awakening - Abbadi, Aïcha; Heckmann, Katharina (Berlin : [s.n.], 2020)
The authors of this publication have initiated the critical fashion collective DEEP FASHION SOCIETY, reflecting an emerging cultural shift among fashion practitioners who seek to incorporate observations about the fashion world into their practice, as a critical commentary and to offer new ways of seeing and experiencing fashion. (text publisher)
As fashion's enthusiasts and practitioners progress deeper and deeper into the fashion world, their perception becomes altered forever. A sudden awakening from the fashion dream marks a turning point in their lives. Entering into a deep fashion state of mind allows them to make connections where there were none before and the sudden shift in their thinking opens up a whole new world of possibilities for fashion practice and beyond... (text publisher)
boek
Keywords: Deep Fashion Society